Pectinase production from Aspergillus niger IBT-7 using solid state fermentation - Abdullah, Roheena; Farooq, Iqra; Kaleem, Afshan; Iqtedar, Mehwish; Iftikhar, Tehreema (Bangladesh Journal of Botany, 2018)
Different fungal strains were isolated from the local soil, fruits and vegetables on the basis of pectin hydrolysis. All the isolated strains were identified through microscopic studies and screened for pectinase production using solid state fermentation. The fungal strain identified as Aspergillus niger IBT-7 showed the highest pectinase production. The selected strain was further subjected to optimization through different physical and nutritional parameters to enhance the production of pectinase. Amongst seven different media tested M1 containing rice bran, moistened with Czapek’s nutrient medium showed the highest pectinase production. During optimization maximum pectinase production was achieved after 72 hrs of incubation at 30 ml of moisture content, pH 5.0 and 30°C. Xylose (1.5%) and yeast extract (1%) proved to be best supplemented carbon and nitrogen sources, respectively which gave the highest pectinase production (39.1 U/ml/min).